1994
DOI: 10.1126/science.7985028
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of an operational MHC class II compartment in nonantigen-presenting cells

Abstract: Professional antigen-presenting cells (APCs) have a distinct compartment in which class II molecules are proposed to acquire antigenic peptides. Genetic evidence suggests that human leukocyte antigen (HLA)-DM, an unusual class II molecule, participates in this process. Peptide acquisition was reconstituted in nonprofessional APCs by transfection of class II, invariant chain (li), and H-2M, the murine equivalent of DM. The H-2M heterodimer appeared in an endosomal compartment, not at the cell surface, and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 40 publications
7
80
0
1
Order By: Relevance
“…3, far right lane), indicating that the lack of stability in the absence of exogenous 48 -61 was caused by their occupation by low affinity peptides. These data are consistent with previous results from our laboratory (25) and from Karlsson and colleagues (35) and corroborate the result of Bikoff et al (13) using splenocytes from DM-deficient mice. However, a previous study using T2.A k concluded that DM was unnecessary for formation of SDS-stable complexes by I-A k (36).…”
Section: Resultssupporting
confidence: 83%
“…3, far right lane), indicating that the lack of stability in the absence of exogenous 48 -61 was caused by their occupation by low affinity peptides. These data are consistent with previous results from our laboratory (25) and from Karlsson and colleagues (35) and corroborate the result of Bikoff et al (13) using splenocytes from DM-deficient mice. However, a previous study using T2.A k concluded that DM was unnecessary for formation of SDS-stable complexes by I-A k (36).…”
Section: Resultssupporting
confidence: 83%
“…In addition, p110␦ mutant B cells showed similar levels of Ag colocalization with H2M (Fig. 6D), a resident of the lysosome/late endosome (MIIC) compartments that catalyze loading of antigenic peptide onto the MHC class II (41)(42)(43)(44). These results suggest that p110␦ mutant B cells are not defective in Ag-BCR internalization or targeting to the MIIC.…”
Section: Ag-bcr Complexes Are Internalized and Targeted To Late Endosmentioning
confidence: 71%
“…As for conventional class II complexes, transient Ii chain/DM associations were previously described in pulse-chase experiments (38,40). Recent studies demonstrate that Ii chain-deficient mice express less DM at steady state (80).…”
Section: Discussionmentioning
confidence: 99%